FENOMENA AKSI MENYAKITI DIRI BAGI REMAJA DALAM MEDIA ONLINE TIRTO.ID ANALISIS TEORI KONSTRUKSI SOSIAL DALAM FENOMENA AKSI MENYAKITI DIRI BAGI REMAJA DALAM MEDIA ONLINE Tirto.id - Prasanti, Dhita; Prihandini, Puji (Jurnal Nomosleca, 2019)
The act of self-injury is an action that will have fatal consequences if left unchecked to occur among teenagers today. Recently, the author saw the proliferation of mass media coverage of cases of depression which led to suicide. Anyone can experience it, especially adolescents who in fact are in a period of emotional development, so even this attracts public attention to examine the main root causes of these actions. But in this article, the author wants to highlight one of the news in Tirto.id's online media which discusses the phenomenon of self-injury for junior high school students that occurred in Riau. In the non-participant observations carried out, the authors see that the online media Tirto.id illustrates the existence of self-injury as a form of depression experienced by junior high school students. The self-destructive actions taken were in the form of slashing one's own hand, slapping himself, hitting the wall, banging his head against the wall, and other acts of self-injury. This phenomenon is relevant to the assumptions contained in social construction theory of reality. Tirto.id said that the phenomenon of self-injury has been widespread, both through social media, videos circulating among junior high school students, that it became viral and constructed as a natural reality carried out by these teenagers, as a form of diversion from depression experienced.Keywords: Phenomenon, Social Construction, Self-Suffering Action, Online Media, Tirto id. DOI:Â https://doi.org/10.26905/nomosleca.v5i2.3226